2023
DOI: 10.1186/s12891-023-07014-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy-guided direct anterior approach total hip arthroplasty provides more accurate component positions in the supine position than in the lateral position

Penglei Chen,
Wangxin Liu,
Cong Wu
et al.

Abstract: Purpose The position of the acetabular and femoral components is critical for stability and wear resistance. The aim of this study is to investigate whether the fluoroscopy-guided direct anterior approach in the supine position (S-DAA) is more helpful in improving the position of acetabular and femoral components than the fluoroscopy-guided direct anterior approach in the lateral decubitus position (L-DAA). Methods A retrospective analysis of 76 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The lateral decubitus position may also play a role in this, Chen et al showed this by comparing 76 cases of fluoroscopy-guided DAA arthroplasty, 38 in supine position and 38 in lateral decubitus. They concluded that the lateral decubitus position resulted in less favorable positioning of the femoral components compared to the supine position [ 37 ]. On the contrary, Rahm et al retrospectively analysed 275 hip replacements using the DAA in supine positions and reported excellent 10-year survivorship (96,8%).…”
Section: Discussionmentioning
confidence: 99%
“…The lateral decubitus position may also play a role in this, Chen et al showed this by comparing 76 cases of fluoroscopy-guided DAA arthroplasty, 38 in supine position and 38 in lateral decubitus. They concluded that the lateral decubitus position resulted in less favorable positioning of the femoral components compared to the supine position [ 37 ]. On the contrary, Rahm et al retrospectively analysed 275 hip replacements using the DAA in supine positions and reported excellent 10-year survivorship (96,8%).…”
Section: Discussionmentioning
confidence: 99%